Various Molecular Arrangements Leading to Different Desolvation Rates: Research on the Stability of 2, 7‐Dibromo‐9H‐carbazole Solvates. Issue 9 (17th June 2021) - Guo, Xuran; Chen, Wei; Wei, Rongli; Sui, Jingchen; Huang, Xin; Wang, Na; Liu, Songqiang; Wang, Ting; Hao, Hongxun
Abstract: The stability of solvates is very important in the field of crystal engineering. Molecular interaction and packing mode are important factors affecting the stability of solvates. In this study, 2, 7‐dibromo‐9H‐carbazole is selected as the model compound to investigate the influence of molecular stacking mode on the stability of solvates. An anhydrous form and five solvates of 2, 7‐dibromo‐9H‐carbazole are obtained by recrystallization. The desolvation phenomena of the five solvates are studied by thermogravimetric analysis, hot stage microscope, and infrared spectroscopy and it is found that the stability of the solvates is N, N ‐dimethylacetamide solvate > dimethyl sulfoxide solvate > N, N ‐dimethylformamide solvate > dioxane solvate > acetonitrile solvate. Crystal structures are analyzed by single crystal X‐ray diffraction and Hirshfeld surface analysis is also applied to analyze the intermolecular interactions in the crystals. The results show that the stability of the five solvates is related to the packing modes of the molecules in the crystal. It is suggested that the solute molecules and solvent molecules in the unstable solvates are arranged in the interlayer mode, while they are arranged in a staggered mode in stable solvates. Abstract : Five solvates and one anhydrate of 2, 7‐dibromo‐9H‐carbazole are obtained. The crystal structure analysis shows that the molecular stacking mode of unstable solvates makes the solvent molecules easy to escape, while the cage structure of the stable solvate makes the solvent molecules difficult to escape.